W2,p-Solvability of the Dirichlet Problem for Elliptic Equations with Singular Data - Loredana Caso; Roberta D’Ambrosio; Maria Transirico (Abstract and Applied Analysis)
We give an overview on some results concerning the unique solvability of the Dirichlet problem in W2,p, p>1, for second-order linear elliptic partial differential equations in nondivergence form and with singular data in weighted Sobolev spaces. We also extend such results to the planar case.